2005
DOI: 10.1158/0008-5472.can-05-1696
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ewing's Sarcoma from Primary Bone Marrow–Derived Mesenchymal Progenitor Cells

Abstract: Ewing's sarcoma is a member of Ewing's family tumors (EFTs) and the second most common solid bone and soft tissue malignancy of children and young adults. It is associated in 85% of cases with the t(11;22)(q24:q12) chromosomal translocation that generates fusion of the 5V segment of the EWS gene with the 3V segment of the ETS family gene FLI-1. The EWS-FLI-1 fusion protein behaves as an aberrant transcriptional activator and is believed to contribute to EFT development. However, EWS-FLI-1 induces growth arrest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
283
2
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(307 citation statements)
references
References 48 publications
16
283
2
6
Order By: Relevance
“…11 Another theory has been of origin from fibroblastic reticulum cells that provide a structural supporting function in the stroma of lymph nodes, a subset of cells that have been shown to express desmin. 25 Pluripotent mesenchymal stem cells have been postulated as potential originating cells for several sarcoma types, [26][27][28][29][30][31] and the same suggestion was made for AFH by some authors in the 1980s. 5 Further to the characterization of the recurrent chromosomal rearrangements that result in the EWSR1-CREB1, t(12;22)(q13;q12) EWSR1-ATF1, and t(12;16)(q13;p11) FUS-ATF1 gene fusions, AFH is of course now established as a translocation-associated neoplasm.…”
Section: Etiologymentioning
confidence: 96%
“…11 Another theory has been of origin from fibroblastic reticulum cells that provide a structural supporting function in the stroma of lymph nodes, a subset of cells that have been shown to express desmin. 25 Pluripotent mesenchymal stem cells have been postulated as potential originating cells for several sarcoma types, [26][27][28][29][30][31] and the same suggestion was made for AFH by some authors in the 1980s. 5 Further to the characterization of the recurrent chromosomal rearrangements that result in the EWSR1-CREB1, t(12;22)(q13;q12) EWSR1-ATF1, and t(12;16)(q13;p11) FUS-ATF1 gene fusions, AFH is of course now established as a translocation-associated neoplasm.…”
Section: Etiologymentioning
confidence: 96%
“…mMSCs Two different groups have reported that the expression of EWS-FLI-1 in BM-mMSCs resulted in cell transformation and sarcoma development when implanted into immunodeficient mice [54,55]. These tumors shared some features with Ewing's sarcoma, including cell surface markers and cell morphology.…”
Section: Ewing's Sarcoma Msc Modelsmentioning
confidence: 99%
“…These tumors shared some features with Ewing's sarcoma, including cell surface markers and cell morphology. Interestingly, the expression of EWS-FLI-1 was able to transform mMSCs on its own in one of the studies [55] while secondary hits acquired in culture (i.e. p53 mutation) were required in another study [54].…”
Section: Ewing's Sarcoma Msc Modelsmentioning
confidence: 99%
“…As described above, ectopic expression of EWS/FLI1 results in dramatic changes in morphology and the formation of EFT-like tumors in murine primary bone marrow-derived MPCs but not in murine embryonic stem cells (6,45,52), supporting the notion that MPCs are a plausible cell origin of EFT (45). However, others argue that MPCs cannot be considered progenitors of EFT without further evidence of similarity between human EFT and MPC-EWS/FLI1-induced tumors in mice (29,46).…”
mentioning
confidence: 69%
“…The products of these chimeric genes behave as aberrant transcriptional regulators and are believed to play a crucial role in the onset and progression of EFT (3,36). Indeed, recent studies have revealed that the induction of EWS/FLI1 proteins can trigger transformation in certain cell types, including NIH 3T3 cells (36), C2C12 myoblasts (12), and murine primary bone marrow-derived mesenchymal progenitor cells (MPCs) (6,45,52). However, studies have also indicated that overexpression of EWS/ FLI1 provokes apoptosis and growth arrest in mouse normal embryonic fibroblasts and primary human fibroblasts (10,31), hence hampering understanding of the precise role of EWS/ ETS proteins in the development of EFT.…”
mentioning
confidence: 99%